2020
DOI: 10.5937/ekopolj2004071p
|View full text |Cite
|
Sign up to set email alerts
|

Impact of service quality on satisfaction and loyalty of tourists in rural tourism of Šumadija and Western Serbia

Abstract: The issue of rural tourism service quality does not retain a sufficiently important place in the existing domestic and foreign literature. The purpose of this research in service quality, which is an important initiator of tourist satisfaction and loyalty in rural tourism. The survey was conducted at the beginning of 2020 using a questionnaire-based survey method to 299 respondents. With the purpose of checking the impact of the service quality on the satisfaction and loyalty of tourists in rural tourism of Šu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
2
11
0
1
Order By: Relevance
“…Therefore, this study predicted that satisfaction will play a mediating role in the proposed theoretical model of the TPHSQ. This notion is similar to that of Peric et al (2020) , who reported that visitor satisfaction affects the relationship between service quality and loyalty. Moreover, a positive relationship is observed between service quality and tourist trust ( Jeaheng et al, 2020 ).…”
Section: Literature Reviewsupporting
confidence: 85%
“…Therefore, this study predicted that satisfaction will play a mediating role in the proposed theoretical model of the TPHSQ. This notion is similar to that of Peric et al (2020) , who reported that visitor satisfaction affects the relationship between service quality and loyalty. Moreover, a positive relationship is observed between service quality and tourist trust ( Jeaheng et al, 2020 ).…”
Section: Literature Reviewsupporting
confidence: 85%
“…Research suggests a significant relationship between tourist satisfaction, return intention, and positive word-of-mouth communication (Beeho and Prentice, 1997;Perić and al., 2020)). In this study, we examine this relationship in an effort to build a sustainable and value-generating relationship with domestic tourists.…”
Section: Relationship Between Tourist Satisfaction and Loyaltymentioning
confidence: 99%
“…The literature review on the topic of service quality, satisfaction and loyalty show that the questionnaire survey is the most commonly used instrument to conduct this type of study (Alegre and Garau, 2010). Guided by these reviews, our research instrument was developed based on the models by (Pawitra and Tan, 2003; Owusu-Frimpong and al., 2013; Perić and al., 2020). The questionnaire has five sections.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Destinations, such as the Republic of Serbia, want to restart tourism for economic survival (Valeri & Baggio, 2020). The quality of the destination and risk avoidance is an important element for the loyalty and re-visits of tourists (Perić et al, 2020) because in tourism the satisfaction of tourists relies on their experience during the trip (Perić et al, 2018). Due to the future of the global tourism industry, the effect of the pandemic on travel and tourism is particularly worrying.…”
Section: Covid-19 Health Crisis: Perceived Risk and Travel Intentionmentioning
confidence: 99%